TYPE 2 NEOVASCULARIZATION SECONDARY TO AGE-RELATED MACULAR DEGENERATION IMAGED BY OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue 11 (November 2015) - El Ameen, Ala; Cohen, Salomon Y.; Semoun, Oudy; Miere, Alexandra; Srour, Mayer; Quaranta-El Maftouhi, Maddalena; Oubraham, Hassiba; Blanco-Garavito, Rocio; Querques, Giuseppe; Souied, Eric H.
Abstract : Purpose: Optical coherence tomography angiography is a novel and noninvasive technique for imaging retinal microvasculature by detecting changes in reflectivity that is related to blood flow. The purpose of this study was to describe Type 2 neovascularization characteristics in age-related macular degeneration using optical coherence tomography angiography. Methods: Fourteen eyes of 14 consecutive patients with Type 2 neovascularization were prospectively included. All patients underwent a complete ophthalmological examination, including color and infrared fundus photography, fluorescein and indocyanine green angiography, spectral domain optical coherence tomography angiography, and optical coherence tomography angiography. Results: In all cases, Type 2 lesions could be detected by optical coherence tomography angiography, presenting as a hyperflow lesion in the outer retina, with a glomerulus (4/14) or medusa shape (10/14), surrounded by a dark halo. The superficial layer and the deep retina showed no abnormal flow. Surprisingly, the Type 2 lesions could also be observed in the presumed choriocapillaris layer. These glomerulus- or medusa-shaped lesions were connected, in 10/14 eyes, to a thicker main branch, which seemed to continue deep into the choroidal layers. Conclusion: Optical coherence tomography angiography may be a new imaging method for the diagnosis of Type 2 neovascularization in clinical routine. However, the specificity of the features needs to be investigated in further studies. Abstract : In a prospective, monocentric study including 14 consecutive age-related macular degeneration patients with Type 2 neovascularization, optical coherence tomography angiography showed a hyperflow lesion not only in the outer retina but surprisingly also in the choriocapillaris layer with a glomerulus- (4/14) or medusa-shaped complex (10/14), surrounded by a dark halo.